2007
DOI: 10.1111/j.1467-8624.2007.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Cognitive and Emotional Responses to Marital Hostility

Abstract: Early adolescents' (11-14 years) responses to marital hostility were examined in a sample of 416 families. The cognitive-contextual perspective and emotional security hypothesis guided the study and 9 adolescent responses were identified. Prospective associations were examined in several structural equation models that included adolescent problems as outcomes. Self-blame and perceived threat uniquely mediated the association between Year 1 marital hostility and Year 3 adolescent externalizing problems (p<.05).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
122
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 53 publications
12
122
3
Order By: Relevance
“…This is consistent with reports in the literature which suggest frequent and hostile parental conflict is related to the presence in the children of aggressive behavior toward peers at school (Buehler et al, 2007;Kitzmann et al, 2003;Lee et al, 2015). Parental conflict explains the presence of aggressive Note.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with reports in the literature which suggest frequent and hostile parental conflict is related to the presence in the children of aggressive behavior toward peers at school (Buehler et al, 2007;Kitzmann et al, 2003;Lee et al, 2015). Parental conflict explains the presence of aggressive Note.…”
Section: Discussionsupporting
confidence: 92%
“…This conflict, which has a negative effect on parenting practices, favors the presence of externalized behavior problems (aggression, bullying) and internalization (depression, anxiety) in children (Buehler, Lange, & Franck, 2007;Kitzmann, Gaylord, Holt, & Kenny, 2003;Lee, Wesbecher, Lee, & Lee, 2015). It also damages adolescents' and children's sense of family identity and safety, effects that are exacerbated when conflict is common, if it is handled in a hostile way and when it relates to or involves children (Cummings, Goekemorey, & Papp, 2003;Lindsey, Colwell, Frabutt, & McKinnon-Lewis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we could assume that the parents in the ''High marital conflict group'' could use a series of destructive conflict strategies, such as verbal hostility, physical aggression, nonverbal anger, and withdrawal. These strategies, by eliciting negative appraisals (perceived threat and self-blame) and emotional and behavioral reactions from children (e.g., anger, sadness, and behavior dysregulation), may make children more vulnerable to developing internalizing and externalizing problems (e.g., Buehler et al 2007;Camisasca et al 2014;Fosco and Grych 2008;Katz and Low 2004). Conversely, we could assume that, in the family et al (2009, 2013) and, in order to better explain these results, future research should ascertain the relative incidence of destructive or constructive conflict tactics because recent work suggests that most couples engage in both constructive and destructive marital conflict tactics during everyday conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…This type of conflict tactic elicits positive emotional reactions (e.g., happiness) from children and reduces the probability of children having aggressive tendencies (Cummings et al 2004). In contrast, the use of destructive tactics, such as verbal hostility, physical aggression, nonverbal anger, and withdrawal, elicits negative emotional and behavioral reactions from children Goeke-Morey et al 2003) and may make them more vulnerable to developing adjustment problems (Buehler et al 2007;Fosco and Grych 2008). Indeed, several empirical studies have long shown that exposure to high levels of marital conflict is associated with of a wide variety of difficulties for children and adolescents, including externalizing behaviors and internalizing problems, social maladjustment, and deficits in cognitive competency (Camisasca et al 2013a(Camisasca et al , b, 2014Davies and Cummings 1994;Fosco and Grych 2008;McCoy et al 2009McCoy et al , 2013Pendry and Adam 2013).…”
Section: Introductionmentioning
confidence: 93%
“…In a sample of fathers who had been arrested for domestic violence, there was a tendency for men's interpersonal hostility to be associated with their reports of their children's overall emotional and behavioral functioning (Febres et al 2014). In a community sample, emotional dysregulation and self-blame mediated the association between interparental hostility measured when children were in sixth grade and youth internalizing problems 2 years later (Buehler et al 2007). Correspondingly, parent hostility was one of the best predictors of youth who recovered from phobic and anxiety disorders after receiving exposure-based cognitive and behavioral treatment as compared to children who did not (Berman et al 2000).…”
Section: Introductionmentioning
confidence: 96%